Level of surgery does not affect the reamputation rates in patients with diabetic foot ulcers requiring amputation of the ankle or foot (Annals of Medical Research, 2021)
Aim: In this retrospective study, we aimed to evaluate the effect of amputation level on reamputation rates and need for additional surgeries in patients with type 2 diabetes mellitus.Material and Methods: Patients who were amputated at the foot and ankle level for diabetic foot ulcers between 2010 and 2019 at our institution were retrospectively evaluated. Amputation types (proximal to distal; Syme, Boyd, Chopart, Lisfranc, Transmetatarsal), previous amputations, need for additional surgeries and reamputations were noted. The effect of amputation level on reamputation and reoperation rates was statistically evaluated. Results: Thirty-one patients (27 male, 4 female) with mean age of 65 years (range 45-84) were included. Reamputation rates for Syme, Boyd, Chopart, Lisfranc and Transmetatarsal (TMA) amputations were 50%, 55%, 50%, 66% and 75% respectively. Fifty percent of the cases in the Syme group, 78% in the Boyd group, 75% in the Chopart group, 83% in the Lisfranc group and 75% in the TMA group required repeating surgeries. There was no significant difference in terms of reamputation and reoperation rates between amputation levels. Conclusion: If the level of amputation is determined based on viability of the skin flap that would be required for soft tissue cover and confirmed intraoperatively by inspecting the perfusion of the stump, the amputation level does not have influence on reamputation rates at the foot and ankle. When performing this irreversible procedure, the patient must be well informed about the possible functional outcomes, prosthesis options and reamputation rates.